DIGITAL-BASED AND SUSTAINABLE TOURISM VILLAGE DEVELOPMENT PLANNING INPAPA GARANG VILLAGE, LABUAN BAJO - Setyawati, Rahmi (UI Scholars Hub, 2022)
Indonesia as a maritime axis, of course, will not be separated from maritime culture and technology. The maritime axis is a development paradigm needed by maritime-based regions such as Labuan Bajo. Maritime culture should be the original culture of Indonesia, because Indonesia is an archipelagic country. However, the development of tourist villages located on the coast requires a special planning program that is in accordance with the characteristics of the community, geography, and socio-culture so that tourism development is sustainable. This study aims to create a digital-based and sustainable independent tourism village development program. The concept used is sustainable tourism, marine tourism village and through community development to buildhuman capital. The creation of human resource capacity, in this case local communities, who do understand these maritime attitudes and values. By combining the concept of maritime culture and the concept of community development. The results of research for the development of marine tourism villages require an approach with aspects of digitalization technology that can be used as an information center containing the results of internalizing maritime culture with local wisdom and infrastructure facilities to accelerate economic growth. Digitization is used for the community, one of which is fishermen, business actors in the tourism sector and small and medium businesses through digital platforms, so that they can create an information data network in the form of big data as a means ofeconomic digitization infrastructure, and human capital development through human resource development and digital literacy. Products in the form of physical, consisting of arts, culinary arts, building arts (Architecture) and non-physical in the form of norms and values that are in accordance with maritime culture, which then becomes an information attraction both from the tourism element and the implementation of maritime culture which has economic value. for the development of sustainable marine tourism villages.